A GRANDMASTER OF SCIENTIFIC RESEARCH (toward the 90th anniversary of V.M. Yakovenko) - Yu. O. Averkov; M. M. Beletski; O. O. Kostenko; V. M. Kuklin; P. M. Melezhik; I. E. Pochanina; M. T. Cherpak; V. O. Yampolski (Radio Physics and Radio Astronomy)
This paper is devoted to the memory of Volodymyr Methodyevich Yakovenko, an outstanding scientist in the field of solid-state radio physics, Honored Worker of Science and Technology of Ukraine, Full Member of the National Academy of Sciences (NAS) of Ukraine, Honorary Director of the O.Ya. Usykov Institute for Radiophysics and Electronics (IRE) within the NAS. At the IRE, Dr. Yakovenko founded a scientific school that is well-known for its studies of charged particles’ interaction with electromagnetic fields in inhomogeneous conducting media. In addition, he initiated research in a new branch of today’s solid state physics, specifically investigation of plasma instabilities in semiconductors that occur because of heating of conduction electrons by the existing elecromagnetic fields.